1999
DOI: 10.1212/wnl.53.9.1998
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of depressive symptoms in the preclinical phase of AD

Abstract: Depressive symptoms are elevated preclinically in AD, and this elevation is not merely a by-product of self-perceived cognitive difficulties. Thus, depressive symptoms may be part of the preclinical phase in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
3
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(165 citation statements)
references
References 35 publications
6
155
3
1
Order By: Relevance
“…[30][31][32] Fifthly, the mtDNA polymorphism is a non-specific genetic risk factor. Recently, it has been suggested that depressive symptoms are elevated in the preclinical phase of Alzheimer's disease 123 and patients with mood disorders have a higher risk of dementia. 124 Although the contribution of different mitochondrial polymorphisms to Alzheimer's disease and bipolar disorder are described in the literature, they might be duplicating each other.…”
Section: Methodological Problemsmentioning
confidence: 99%
“…[30][31][32] Fifthly, the mtDNA polymorphism is a non-specific genetic risk factor. Recently, it has been suggested that depressive symptoms are elevated in the preclinical phase of Alzheimer's disease 123 and patients with mood disorders have a higher risk of dementia. 124 Although the contribution of different mitochondrial polymorphisms to Alzheimer's disease and bipolar disorder are described in the literature, they might be duplicating each other.…”
Section: Methodological Problemsmentioning
confidence: 99%
“…Older people with depression may be at increased risk for dementia [56]. Alternatively, depression may simply be a common early AD presentation.…”
Section: Potentially Reversible Syndromesmentioning
confidence: 99%
“…Although the main function of AVP is the antidiuresis in kidney, it plays a key role in hypothalamo-pituitary-adrenocortical (HPA) axis regulation, thereby in stress-related psychiatric diseases, like depression [31]. Depression can also be one of the earliest symptoms of AD [2]. Half of the AD patients suffer from minor or major depressive disorder, too [47,56].…”
Section: Introductionmentioning
confidence: 99%